Determination of amphetamines in hair samples using microextraction by packaged sorbent and gas chromatography coupled to mass spectrometry - Pires, Bruno Miguel Pinheiro (2023)
Different extraction and clean-up protocols have been used for Amphetamine-type psychostimulants (ATS) determination in hair. Microextraction by packed sorbent (MEPS) is a miniaturized version of solid-phase extraction (SPE) which has been applied to determine a number of drugs in hair (e.g., opiates, cocaine, ketamine, etc.). However, concerning Amphetamine-type psychostimulants, MEPS has only been used in hair for the determination of amphetamine (AMP) and methamphetamine (MAMP). The aim of this work was the development and validation of a method to determine AMP, MAMP, 3,4-methylenedioxyamphetamine (MDA), 3,4- methylenedioxymethamphetamine (MDMA), 1-(1,3-benzodioxol-5-yl)propan-2- yl(ethyl)amine (MDE) and N-methyl-1-(1,3-benzodioxol-5-yl)-2-aminobutane (MBDB) in hair using MEPS for sample clean-up. Hair (50 mg) was incubated with NaOH 1M at 45 ºC overnight, after which HCl 10M was added for neutralization and the solution was centrifuged. The MEPS procedure for extract clean-up was optimized using the Design of Experiments (DoE) approach, and the final steps were: conditioning (1 x 250 µL of methanol and 1 x 250 µL of deionized water); loading (18 x 100 µL); and elution (7 x 100 µL of 2% NH4OH in acetonitrile). To the eluted extract, 30 µL of MBTFA was added, and extracts were evaporated to dryness, following microwave-assisted derivatization with 50 µL of MBTFA. A gas chromatography coupled to mass spectrometry (GC-MS) system was used for determination. The MEPS procedure resulted in recoveries of 8-14% for AMP, 14-20% for MAMP, 10-15% for MDA, 18-28% for MDMA, 25-43% for MDE and 34-52% for MBDB, in the linear range of 0.2 - 5.0 ng/mg. Precision and accuracy of the developed method were in accordance with the statements of international guidelines for method validation. This is the first analytical method using MEPS coupled to GC-MS to determine the selected amphetamines in hair samples, proving to be a great alternative to the classic procedures, being rapid, ecofriendly and less expensive.